Enhancing Ship Stability: A Comparative Analysis of Single and Double Chine Hull Configurations of Semi-Planning Hull at High Speed - Ghyferi, Andi Abdullah; Bahatmaka, Aldias; Naryanto, Rizqi Fitri; Won, Lee Sang; Cho, Joung Hyung (Universitas Sebelas Maret, 2024)
Ship stability could be considered one of the defining aspects of marine transport, as it directly influences the safety and performance of the ship. Past works have found hull geometry critical in the stability issue; however, the impact of various Chinese configurations under different operation scenarios is missing. This paper seeks to address this gap by studying the effects of Chinese single and double geometries on stability, primarily concerning trimming by stern angles in compliance with the High-Speed Craft (HSC) 2000. Annex 8: Monohull Intact Stability Criteria. Stability calculations using Maxsurf software were done concerning angles of the steady heel, the area under the righting levers (GZ) curve, maximum GZ, and initial transverse metacentric height (GMt). The study showed that both Chinese configurations conformed to the prescribed stability standards. Still, the double Chinese configuration showed better results in terms of stability at a 2-degree heel angle, with a GZ value of 1.692 and the highest GMt value in a steady state. Therefore, the research establishes enhanced stability benefits that the users stand to benefit from by adopting double chine configurations relative to single chine styles.